A Reflection on #Metoo, a Story of Sexual Assault and Victimhood in India - Shromona Das (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2020)
This work contains illustrations of Shromona Das, who was seven when she was sexually abused by her uncle. Years later suffering silently with the burden of keeping her trauma a secret, Shromona has finally gathered the strength to call out her abusers via her powerful illustrations.